(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Listihani L, Ariati PEP, Yuniti IGAD, Selangga DGW. 2022. The brown planthopper (Nilaparvata lugens) attack and its genetic diversity on rice in Bali, Indonesia. Biodiversitas 23: 4696-4704. The brown planthopper (Nilaparvata lugens) is an important pest on rice crops in Indonesia. The genetic diversity of BPH isolates in western Indonesia has been extensively reported, whereas eastern Indonesia isolates have not been reported. This research aims to analyze genetic diversity and evaluate the BPH attack’s intensity on Bali rice plants. The research method used was an observation of attack percentage, population dynamics, attack intensity, and genetic diversity of BPH in 9 districts in Bali (Badung, Gianyar, Klungkung, Bangli, Karangasem, Tabanan, Denpasar City, Buleleng, and Jembrana). Molecular identification was carried out on N. lugens DNA in the mtCOI fragment. BPH attacks of >50% were found in the districts of Gianyar, Bangli, Jembrana, and Badung. The BPH population was primarily found in Ciherang and IR-64 varieties of rice in the Badung Regency, with 43.67 BPH per rice hill. In general, rice varieties grown in all observation locations were susceptible to BPH, such as Ciherang, IR-64, Inpari 32, and Situbagendit. In the Ciherang and IR-64 varieties, the highest attack intensity average value reached 30%. The sequence of N. lugens isolate from Bali Jembrana showed the highest nucleotide and amino acid homology with N. lugens isolate FSD-034 from Pakistan (MK301229) biotype Y of 99.5 -99.74% and 100%, respectively. This study found N. lugens biotype Y in rice plants for the first time in Indonesia. This study reported that Rice varieties Situbagendit and Inpari 32, previously resistant to BPH, are reported as susceptible to BPH.